Childhood Stunting in East Java: A Health System Structural Analysis Using Generalized Structural Equation Modeling - Ayudina Larasanti; Ardiana Fatma Dewi; Alifani Faiz Faradhila (PubHealth Jurnal Kesehatan Masyarakat, 2026)
Despite decades of investment in health service infrastructure and social protection programs, the pathways through which service utilization, insurance coverage, and poverty jointly shape stunting risk among children under five in East Java remain poorly understood at the structural level. This study analyzed data from the Indonesian Nutritional Status Survey (SSGI) 2024 among 20,304 children under five in East Java, employing Generalized Structural Equation Modeling (GSEM) to simultaneously estimate the direct, indirect, and total effects of health service utilization, insurance coverage, household poverty, and sociodemographic characteristics on stunting risk. GSEM findings demonstrated that lacking health insurance (B = 0.273; 95% CI: 0.194–0.352; p < 0.001) and household poverty (B = 0.137; 95% CI: 0.107–0.167; p < 0.001) exerted significant direct effects on stunting, while health service utilization frequency (B = 0.037; 95% CI: −0.067 to 0.141; p = 0.489) and service type diversity (B = −0.001; 95% CI: −0.102 to 0.099; p = 0.987) showed no significant direct effects, suggesting that service contact alone is insufficient without accompanying improvements in care quality. Child age emerged as a strong cumulative predictor of stunting, and household poverty operated through both direct and indirect pathways mediated by insurance status and service utilization. These results indicate that stunting reduction in East Java demands simultaneous action on service quality, insurance coverage equity, and upstream poverty alleviation.